Physicochemical characteristics of the Chauya lagoon (May 2015-April 2016) - Contreras S., Guadalupe (2017)
The Chauya is a waterbody located in the district of Masisea (Ucayali, Peru) in an area of 34.77 km2. The lagoon is important for the commercial fishing fleet of Pucallpa and is part of the Regional Conservation of Imiria. The Fisheries Management Plan was developed in 2008, but it has not followed up. The aim of this study was to assess the physicochemical characteristics of the lagoon and its comparison with the initial study. The results showed that the physicochemical characteristics of the environment and water were like in the original Fisheries Management Plan, and without significant differences in terms of ambient and water subsurface temperature, pH, ammonia, CO2, chlorides, water hardness, and dissolved oxygen in water.